The effect of attenuating dietary phosphate restriction on blood ionized calcium concentrations in cats with chronic kidney disease and ionized hypercalcemia - Rebecca, FG; van den Broek, DHN; Chang, YM; Biourge, V; Elliott, J; Jepson, RE (Journal of Veterinary Internal Medicine, 2025)
Background Hypercalcemia is commonly observed in cats with azotemic chronic kidney disease (CKD). Dietary phosphate restriction is considered standard of care but may contribute to the development of hypercalcemia. The optimal dietary management strategy for these cats is unclear. Objectives To describe the effect of feeding a moderately phosphate-restricted diet (MP; 1.5 g/Mcal phosphorus; Ca : P ratio, 1.3) to cats with concurrent azotemic CKD and ionized hypercalcemia. Animals Client-owned cats with ionized hypercalcemia (ionized calcium [iCa] concentration >1.4 mmol/L) at diagnosis of CKD (n = 11; baseline hypercalcemics) or after CKD diagnosis while eating a phosphate-restricted clinical renal diet (0.8 g/Mcal phosphorus; Ca : P ratio, 1.9; n = 10; RD hypercalcemics). Methods Changes in variables over time, after starting MP at visit 1, were assessed using linear mixed model analysis within each group of cats. Data are reporte as median [25th, 75th percentiles]. Results At visit 1, iCa was 1.47 [1.42, 1.55] mmol/L for baseline hypercalcemics and 1.53 [1.5, 1.67] mmol/L for RD hypercalcemics. Blood iCa decreased (P < .001) when RD hypercalcemics were fed MP, with iCa
Keywords: CKD; diet; feline; renal